2011
DOI: 10.1038/sc.2011.115
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of home-based functional electrical stimulation cycling: case report

Abstract: Study design: Single-subject (male, 64 years of age) case. Objectives: To determine the feasibility of a home-based FES-LEC (functional electrical stimulation lower extremities cycling) program and effects on body composition, quality of life (QOL) and seat pressure mapping in an older individual with spinal cord injured (SCI). Setting: Home-based FES-LEC with internet connection. Southeastern United States. Methods: FES-LEC three sessions per week for 9 weeks in the participant's home and monitored by the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 4 publications
2
26
0
Order By: Relevance
“…6,7 These results also enhance the theory that regular long-term FES-LEC may decrease the risk factors associated with cardiovascular and metabolic diseases. The fact that BMD increased supports the findings of Frotzler et al 3 and provides hope that this activity may also help enhance bone health.…”
Section: Discussionsupporting
confidence: 65%
“…6,7 These results also enhance the theory that regular long-term FES-LEC may decrease the risk factors associated with cardiovascular and metabolic diseases. The fact that BMD increased supports the findings of Frotzler et al 3 and provides hope that this activity may also help enhance bone health.…”
Section: Discussionsupporting
confidence: 65%
“…Previous reports have shown that FES significantly impacts several health variables after SCI, such as lean mass, percentage body fat, and metabolic profiles. 8,9 Gorgey et al 10 found that 12 wks of electrical stimulation to evoke leg extension resistance training resulted in muscle hypertrophy, reduction in visceral adipose tissue, and improvement in metabolic profile in people with SCI. However, applications of FES cycling had been limited largely to clinics and research laboratories, which limited its effectiveness as a rehabilitation intervention to promote physical activity and continuity of care after SCI.…”
mentioning
confidence: 98%
“…Considering the current findings, bioengineers and manufactures should consider expanding the existing stimulation parameters in therapeutic stimulators. Because reliance on portable units to conduct home-exercise program may be a costeffective compared to expensive FES bikes [34]. The smaller muscle size after SCI compared to able-bodied individuals can result in full muscle activation accompanied with increasing the evoked torque that may result in significant muscle damage or fracture of osteoporotic bones.…”
Section: Discussionmentioning
confidence: 99%